Lessons learned from the implementation of integrated serosurveillance of communicable diseases in the Americas - Martha-Idalí; Luis Gerardo Castellanos; Ana Morice; Maria Paz Ade; Gloria Rey-Benito; Gretchen M. Cooley; Heather M. Scobie; Ryan E. Wiegand; Melissa M. Coughlin; Diana L. Martin (Pan American Health Organization, 2023)
Objective. Systematize the experience and identify challenges and lessons learned in the implementation of an initiative for integrated serosurveillance of communicable diseases using a multiplex bead assay in countries of the Americas. Methods. Documents produced in the initiative were compiled and reviewed. These included concept notes, internal working papers, regional meetings reports, and survey protocols from the three participating countries (Mexico, Paraguay, and Brazil) and two additional countries (Guyana and Guatemala) where serology for several communicable diseases was included in neglected tropical diseases surveys. Information was extracted and summarized to describe the experience and the most relevant challenges and lessons learned. Results. Implementing integrated serosurveys requires interprogrammatic and interdisciplinary work teams for the design of survey protocols to respond to key programmatic questions aligned to the needs of the countries. Valid laboratory results are critical and rely on the standardized installment and roll-out of laboratory techniques. Field teams require adequate training and supervision to properly implement survey procedures. The analysis and interpretation of serosurveys results should be antigen-specific, contextualizing the responses for each disease, and triangulated with programmatic and epidemiological data for making decisions tailored to specific population socioeconomic and ecologic contexts. Conclusions. Integrated serosurveillance as a complementary tool for functional epidemiological surveillance systems is feasible to use and key components should be considered: political engagement, technical engagement, and integrated planning. Aspects such as designing the protocol, selecting target populations and diseases, laboratory capacities, anticipating the capacities to analyze and interpret complex data, and how to use it are key.